A novel resin cement to improve bonding interface durability. Issue 37 (26th August 2022) - He, Xi; Yu, Shiyang; Wang, Huimin; Tian, Zilu; Zhang, Jiahui; Zhao, Ying; Gong, Haihuan; Shi, Zuosen; Cui, Zhanchen; Zhu, Song
Abstract : Bonding failure is one of the main causes of failure of dental restorations. Abstract : Bonding failure is one of the main causes of failure of dental restorations. The bonding strength, aging resistance, and polymerization shrinkage of cement can affect the stability of the bonding interface and lead to marginal microleakage. To reduce the bonding failure rate of restorations, a novel polyurethane (PU) cement was designed to improve the mechanical properties, hydrophobicity, degree of conversion (DC), polymerization shrinkage, bond strength and aging resistance of cement by introducing isophorone diisocyanate (IPDI) and hydroxyethyl methacrylate (HEMA) and adjusting the polyester : polyether ratio to increase the degree of cross-linking. Experimental results verified that the novel PU could increase the mechanical properties and thermal stability of the cement, reduce polymerization shrinkage during the curing reaction, improve the bonding performance and DC, endow the cement with hydrophobic properties, and improve its ability to resist aging in the salivary environment to maintain the long-term stability of interfacial bonding under the influence of comprehensive factors. The results of this study provide a new direction and insights to reduce microleakage and improve the success rate of restorations.